Performing Modernism A Jewish Avant-Garde in Bucharest - Chiriac, Alexandra (De Gruyter, 2022)
The book examines the reach of modernism in design and performance in Romania between the two world wars, focusing on remarkable Jewish avant-garde artists located in Bucharest. Based on extensive new research, it shows how Romania's capital was connected to Berlin, Riga and Chicago through modern design and experimental Yiddish theatre, highlighting the contribution of Jewish cultural production to avant-garde movements in Europe and beyond.